ANALISI FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN INSOMNIA PADA WANITA MENOPAUSE DI POSYANDU WILAYAH KERJA PUSKESMAS PUNTI KAYU TAHUN 2021 - Rima Syafaria; Titin Dewi Sartika; Turiyani; H Hazairin Efendi (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Menopausal women will experience several problems, one of which is sleep disorders (Insomnia). Insomnia is characterized by difficulty in initiating sleep. Various factors are thought to have a significant relationship with the occurrence of insomnia in postmenopausal women, including response to disease, lifestyle and anxiety levels. The purpose of this study was to determine the factors associated with the incidence of insomnia in postmenopausal women at the Posyandu in the Punti Kayu Palembang Health Centre in 2021. The research method used a survey Analytical by using design cross sectional, the sampling of this research used total sampling technique with a total sample of 63 people. Collecting data using a questionnaire sheet. The analysis used is analysis univariate and bivariat eusing testchi-square. The univariate results showed that 37 (58.7%) menopausal women experienced insomnia, 27 (42.9%) menopausal women, 27 (42.9%) postmenopausal women, and 33 (52.4%) menopausal women experienced poor lifestyle. anxiety as many as 30 (47.6%) postmenopausal women. ResultsIt is known that there is a relationship between response to disease and the incidence of insomnia in postmenopausal women with (p value = 0.000), there is a relationship between lifestyle and the incidence of insomnia in menopausal women with (p value = 0.000), there is a relationship between anxiety levels and the incidence of insomnia in menopausal women with (p value = 0.003). The conclusion of this study is that there is a relationship between response to disease, lifestyle, anxiety levels with the incidence of insomnia in postmenopausal women at the Posyandu in the Punti Kayu Health Centre in 2021. This study is expected to encourage postmenopausal women to maintain their health, change lifestyle habits and consume water, and reduce anxiety.